Dampak Sosial Ekonomi Alokasi Dana Desa Terhadap Perekonomian Masyarakat Desa Di Desamrawan Kecamatan Mayang Kabupaten Jember - moch iqbal hasan; Sunlip Wibisono; Fivien Muslihatinningsih (UPT Penerbitan Universitas Jember, 2021)
Abstract The Village Fund Allocation (ADD) given to villages in the Jember Regency region gives greater hope for the realization of equitable development. The implementation of the ADD policy provides a significant change, villages that used to get a budget from a very limited central government that is centrally managed by government agencies above, the village now has a large enough budget and is given the authority to manage it independently. The purpose of this study was to: (1) determine the condition of the Mrawan village community before and after the ADD, (2) determine the socioeconomic impact of the ADD on the economy of the Mrawan village community. This research can be classified into descriptive research types. This research was conducted in Mrawan Village, Mayang District, Jember Regency. Data collection is done through interviews, observations, and documentation. Data analysis technique used is data analysis with qualitative methods with the steps of data collection, data reduction, data presentation and drawing conclusions. The results showed that after ADD the condition of the community around the village of Mrawan earned additional income by participating in the development activities provided by the Village. In addition, the social impacts caused by ADD include increasing community income, better living conditions, better village facilities. Keywords: village fund allocation, policy impact, social economic impact.